Overnight monitoring reveals the behavioral rhythms of a geriatric male elephant: an animal-centered case study of rest and stereotypy - McGuire, Alena; Kienlen, Michelle; Emory, Rachel; LaDue, Chase A. (Frontiers in Conservation Science, 2024)
Introduction Monitoring overnight behavior is important in assessing the overall wellbeing of ex-situ elephant populations, with recumbent rest and stereotypy as key indicators of welfare. However, there have been few studies that address the overnight behavior of singly housed male elephants with a history of stereotypy. We conducted an opportunistic case study of the overnight behavior (i.e., rest and stereotypy) of a singly housed geriatric male Asian elephant at the Oklahoma City Zoo to identify his overnight behavioral rhythms in response to physiological (musth) and environmental changes (habitat access, automatic timed feeders) and guide management strategies. Methods Infrared cameras were utilized to conduct continuous focal-animal sampling of the elephant’s behavior between 20:00 and 08:00 in indoor and outdoor habitats. Sampling occurred from January 2023 to October 2023, with a total of 179 overnight observations. Results The elephant exhibited recumbent rest for 175.66 ± 6.80 (mean ± SE) minutes per night and was engaged in stereotypy for 175.88 ± 9.68 minutes per night. While there was no significant relationship between stereotypy and the sexual state of musth, musth was associated with reduced durations of recumbent rest. Access to both indoor and outdoor habitats was significantly related to decreased stereotypy compared to indoor-only treatments. Recumbent rest occurred most frequently between 02:00 and 05:00, and stereotypic behavior was most common between 06:00 and 08:00. Contrary to our expectations, automatic feeders did not significantly reduce stereotypy. Discussion The results of this study provide insight into the behavioral patterns of a geriatric male Asian elephant, demonstrating the importance of implementing an animal-centered approach to enhance animal wellbeing. As the zoo-housed Asian elephant population grows and continues to age, this case study emphasizes the importance of developing comprehensive welfare strategies for the elephants in our care.